Effects of ZMA supplementation on the relationship of zinc and magnesium to body composition, strength, sprint performance, and metabolic and hormonal profiles - Wilborn, C.; Baer, J.; Campbell, B.; Thomas, A.; Slonaker, B.; Vacanti, T.; Marcello, B.; Kerksick, C.; Rasmussen, C.; Taylor, L.; Mulligan, C.; Rohle, D.; et al. (Sports Nutrition Review Journal, 2004)
Zinc and magnesium deficiencies have been reported to diminish serum testosterone levels, impair immune function, and decrease strength in athletes. For this reason, zinc, magnesium aspartate (ZMA) supplementation has been purported to increase zinc and magnesium status and thereby improve strength and anabolic hormonal status. PURPOSE: The purpose this study was: 1.) to examine the relationship of plasma zinc and magnesium status on strength, body composition, and markers of anabolic/catabolic status; and, 2.) to determine whether ZMA supplementation during training influences this relationship. METHODS: 26 resistance-trained males (26±9 yrs; 178±6 cm, 85±12 kg, 18±6.9 % body fat) participated in this study. Subjects were matched according to FFM and randomly assigned to ingest in a double blind manner either a dextrose placebo (P) or ZMA (Z-MASSPM™, Cytodyne Technologies, Lakewood, NJ) 30-60 minutes prior to going to bed during 8-weeks of standardized training. At 0, 4, and 8-weeks of training, subjects donated fasting blood samples, had DEXA body composition determined, and performed 1RM strength tests, 80% of 1RM muscle endurance tests, and Wingate anaerobic capacity sprint test. Data were analyzed by repeated measures ANOVA and Pearson correlation analysis. Data are presented as means ± standard deviations for the P and ZMA groups at 0, 4, and 8 weeks, respectively. ESULTS: Plasma zinc levels were within normal ranges and were non-significantly increased by 12-17% after supplementation in the ZMA group (1.08±0.2, 1.02±0.14, 1.07±0.25; 1.04±0.24, 1.15±0.27, 1.20±0.23, ìg/ml, p=0.12). Magnesium levels were also within normal ranges and were not significantly affected by supplementation (26.5±2.3, 27.2±2.5, 27.6±2.3; 26.9±1.7, 28.0±2.7, 26.9±3.6, ìg/ml, p=0.40). Baseline zinc levels significantly correlated with AST (-.39, p=0.04), neutrophils (.45, p=0.02), and monocytes (-.42, p=0.03) but did not significantly correlate (p>0.05) with body weight, fat free mass, body fat, 1RM bench press, 1 RM leg press, muscle endurance, sprint capacity, IGF-1, total testosterone, free testosterone, cortisol, growth hormone, blood urea nitrogen, creatinine, ratio of BUN/creatinine, CK, LDH, uric acid, ALT, GGT, triglycerides, total cholesterol, LDL cholesterol, sodium, potassium, chloride, calcium, total protein, albumin, globulin, bilirubin, alkaline phosphatase, glucose, WBC, RBC, Hgb, hematocrit, MCV, MCH, MCHC, RDW, platelets, lymphocytes, eosinophils, or basophils. Baseline magnesium levels significantly correlated with body weight (-0.42, p=0.03), scanned mass (-0.42, p=0.03), body fat (-0.46, p=0.02), percent body fat (-0.41, p=0.04), HDL (0.52, p=0.006), the CHL/HDL ratio (-0.41, p=0.04), total protein (0.47, p=0.02), glucose (-.45, p=0.02), and basophils (.46, p=0.02) with no other significant correlations observed in remaining variables assessed. After 4 weeks supplementation, zinc levels significantly correlated with CK (-0.41, p=0.04) and platelets (.44, p=0.02) while magnesium levels correlated with cortisol (0.43. p=0.03). After 8 weeks of supplementation, zinc levels correlated with sodium (0.42, p=0.03), globulin (-.48, p=0.01), the ratio of albumin/globulin (0.58, p=0.002), and Hgb (.41, p=0.04) while magnesium levels correlated with chloride (-.42, p=0.03) and lymphocytes (.48, p=0.01) levels. Although significant training adaptations were observed, ZMA supplementation did not significantly affect changes in body composition, strength, sprint performance, or hormonal profiles. CONCLUSION: Results indicate: 1.) experienced weight lifters had normal zinc and magnesium status; 2.) ZMA supplementation non-significantly increased baseline zinc levels by 12-17% with no significant effects on magnesium levels; 3.) baseline and post-supplementation zinc levels did not significantly correlate with body composition, hormone profiles, strength, or sprint performance variables; 4.) baseline magnesium levels correlated with a number of body composition and metabolic markers but most of these correlations became non-significant after supplementation; 5.) supplementation positively and negatively influenced the relationship of zinc and magnesium to a number of variables; and, 6.) although trends were observed, ZMA supplementation appears to have limited value on body composition, hormonal profiles, and performance in athletes with normal zinc and magnesium status. Additional research is needed to examine the prevalence of zinc and magnesium deficiencies in resistance trained athletes as well as whether ZMA supplementation has any influence on training adaptations.